“Hoy se pierde un diente mañana un ovario”: Envejecimiento, enfermedad y exceso en Noches de adrenalina de Carmen Ollé - Ponce de León Castilla, Isabel (2025)
This paper proposes, through the examination of excess and the residual elements, that in Carmen Ollé's Noches de adrenalina (1981), erotic desire and sexual consummation question and subvert the registers that are typically used to construct the figure of the “other”, the “old woman”. Aging is represented through exaggerated images of bodily deterioration that construct the poetic voice as an abject “other”, whose body is no longer healthy nor a typical object of erotic desire. The abject is represented not only in the exaggerated manifestations of symptoms but also accompanies the sexual behavior of the poetic voice, which anachronistically contradicts conventional expectations of an older woman.